ANALISIS LITERASI SAINS PADA BUKU PELAJARAN IPAS TINGKAT SEKOLAH DASAR KELAS V KURIKULUM MERDEKA BELAJAR - Apriyanti, Dhea; Dewi, Isti Kumala; Ramadhan, Rully Rachmawati; Wijaya, Tommy Tanu; Hermita, Neni; Diniya, Diniya (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
Science education at the elementary level is an important foundation for building the next generation of people who are broad-minded, think critically, and are able to solve problems. At this level, cultivating curiosity and a passion for science is the main key to growing interest and triggering students' potential to develop themselves in the fields of science and technology. The Science and Technology textbook for class V in the Independent Curriculum offers a new approach to scientific literacy. This research aims to analyze the level of scientific literacy integrated into science textbooks. The study employs a descriptive research design, utilizing content analysis. The data collection instrument is a document review sheet. The research results showed that the Independent Curriculum class V science and science textbook was rated as good. This is proven by various indicators of scientific literacy, such as identifying questions, collecting data, analyzing data, and interpreting data. This research contributes to the development of scientific literacy among students through the science and science textbook for class V, semester II of the Merdeka Curriculum. These findings can also be a basis for textbook developers to improve the quality of scientific literacy in science and science textbooks.